Recent progress of hydrogel-based local drug delivery systems for postoperative radiotherapy - Xie, Yandong; Liu, Mingxi; Cai, Chang; Ye, Chengkun; Guo, Tangjun; Yang, Kun; Xiao, Hong; Tang, Xianglong; Liu, Hongyi (Frontiers in Oncology, 2023)
Surgical resection and postoperative radiotherapy remained the most common therapeutic modalities for malignant tumors. However, tumor recurrence after receiving such combination is difficult to be avoided because of high invasiveness and radiation resistance of cancer cells during long-term therapy. Hydrogels, as novel local drug delivery systems, presented excellent biocompatibility, high drug loading capacity and sustained drug release property. Compared with conventional drug formulations, hydrogels are able to be administered intraoperatively and directly release the entrapped therapeutic agents to the unresectable tumor sites. Therefore, hydrogel-based local drug delivery systems have their unique advantages especially in sensitizing postoperative radiotherapy. In this context, classification and biological properties of hydrogels were firstly introduced. Then, recent progress and application of hydrogels for postoperative radiotherapy were summarized. Finally, the prospects and challenges of hydrogels in postoperative radiotherapy were discussed.